2017
DOI: 10.1016/j.dib.2016.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Data on the radioprotective effect of emodin in vivo and vitro via inhibition of apoptosis and modulation of p53

Abstract: This paper contains the experiment data on the emodin, mice and cell survival rate, mice intestinal tissue H&E and TUNEL staining, the expression of p53 protein in mice small intestine, cell apoptosis, the expression of protein and RNA in vitro included. Data was worked out through MTT assay, Flow cytometry, Western blot, Real-time PCR and Staining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Emodin (1,3,8-trihydroxy-6-methylanthraquinone) is a natural anthraquinone isolated from several Chinese herbs, including Rheum palmatum, Polygonum cuspidatum, and Polygonum multiflorum . Pre-clinical investigations have demonstrated emodin to contain a wide spectrum of pharmacological benefits, including; anti-viral [ 1 ], anti-bacterial [ 2 ], anti-allergic [ 3 ], anti-osteoporotic [ 4 ], anti-diabetic [ 5 , 6 ], anti-inflammatory [ 7 10 ], neuroprotective [ 11 ], hepatoprotective [ 12 ], and anti-tumorigenic [ 13 18 ] properties (Supplementary Table 1 ). In fact, studies by our group have shown that emodin is effective at reducing mammary tumorigenesis given its actions on macrophages [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emodin (1,3,8-trihydroxy-6-methylanthraquinone) is a natural anthraquinone isolated from several Chinese herbs, including Rheum palmatum, Polygonum cuspidatum, and Polygonum multiflorum . Pre-clinical investigations have demonstrated emodin to contain a wide spectrum of pharmacological benefits, including; anti-viral [ 1 ], anti-bacterial [ 2 ], anti-allergic [ 3 ], anti-osteoporotic [ 4 ], anti-diabetic [ 5 , 6 ], anti-inflammatory [ 7 10 ], neuroprotective [ 11 ], hepatoprotective [ 12 ], and anti-tumorigenic [ 13 18 ] properties (Supplementary Table 1 ). In fact, studies by our group have shown that emodin is effective at reducing mammary tumorigenesis given its actions on macrophages [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several natural products with radioprotective abilities have been studied and reported (Table 1) [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The radioprotective mechanism of these natural products has not yet been described in detail, particularly for miRNA modulation.…”
Section: Connection Between Radioprotective Natural Products and Mirnasmentioning
confidence: 99%
“…Since some natural products may exhibit fewer toxic effects than compounds from chemical synthesis, they have become preferable candidates as radioprotectors [2,3]. Recently, several studies have targeted natural bioactive substances as radioprotectors [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, there is a lack of understanding regarding the mechanisms of action for these radioprotective natural products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, emodin is used as a reference drug against Giardia protozoa and it has been a very promising drug. This extract has strong antiinflammatory and antioxidant effects that can be useful in the treatment of osteoporosis, and cardiovascular diseases, CNS, liver, metabolic and respiratory reactions (11,12).…”
Section: Malaria;mentioning
confidence: 99%